Pemanfaatan Obat Tradisional yang Berkembang di Zona Laut Dalam (Batial dan Abisal) - Lisarib, Angelina; Saghawari, Sesilia A.; Ammarie, Nadiyya Summaya; Mait, Mutiara G.; Arari, Stevany Gloria; Umbase, Jansen Reigen Swinli (Jurnal Lentera Farma, 2025)
Indonesia, as an archipelagic country with high marine biodiversity, has great potential in utilizing marine biota as a source of nutrition and medicine. Additionally, microalgae Schizochytrium sp. and Aurantiochytrium sp., which are widely found in Indonesia's mangrove ecosystems, serve as sources of DHA and EPA, which play important roles in human health, particularly in the development of nutritional supplements and the biotechnology industry. Melatonin compound identification was performed using thin-layer chromatography (TLC). Both the sample and standard melatonin compounds were spotted onto a silica gel GF plate. The mobile phase used was an upper-phase mixture of n-butanol: acetic acid: water (12:3:5), and the Rf values of the resulting spots were calculated under UV light observation. The BSLT test on methanol extract of Boergesenia forbesii yielded an LC50 value of 508.74 ppm, indicating the extract contains toxic compounds.